The Myth of the Tropic and the Medicine in European Colonial Experience of Tropical Africa - Navarro Alvarado, Guillermo A. (2016)
This article develops a relational-descriptive analysis between the myth of the tropic and the birth of the tropical medicine, framed in European colonial experience of Tropical Africa. In addition, they addressed the socio-historical conditions of this process and the mythical and pseudoscientific variants that were part of it.